Characterization Methodology for Voltage-Dependent Mobility of Charge Carriers in Graphene FETs Using Single-Device Microwave Measurements - Xiomara Ribero-Figueroa; Anibal Pacheco-Sanchez; Aida Mansouri; Pankaj Kumar; Omid Habibpour; Herbert Zirath; Luca Anzi; Amaia Zurutuza; Roman Sordan; David Jimenez; Francisco Pasadas; Reydezel Torres-Torres (IEEE Journal of Microwaves)
This work proposes a methodology entirely based on processing S-parameters to determine the gate-to-source voltage-dependent mobility of charge carriers in the graphene field-effect transistor channel, without requiring any information about the material properties. Furthermore, regressions from experimental data of transistor arrays with different geometries are not required, thus avoiding uncertainties related to process variations and device-to-device measurement conditions. Hence, one key advantage of this method is its applicability to analyze the performance of different devices under the same operating conditions, or the performance of a single device under varying conditions. As part of the methodology, the effects of the parasitic series resistances associated with the source and drain access paths are considered, thereby overcoming the well-known disadvantage of direct-current methods, where the corresponding de-embedding is cumbersome. This method has been used to determine the carrier mobility in graphene within a gate-to-source voltage range, starting from the Dirac voltage and extending to the region where electron conduction dominates. A small-signal model with the extracted parameter values shows an excellent agreement with the experimental S-parameters up to 20 GHz for the dynamic response of different devices, including two devices that have not been used during parameter extraction. Throughout the development and application of the proposal, a mobility model accounting for the degradation caused by the transverse electric field has been considered.